2022
DOI: 10.1016/j.jbc.2022.101681
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized alkyl phospholipids stimulate sodium transport in proximal tubules via a nongenomic PPARγ-dependent pathway

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 72 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…We previously reported that PPARγ agonists enhance PT Na transport via ERK-mediated non-genomic effects 10,11 . We found that pioglitazone (PGZ), a PPARγ agonist, stimulated NHE and NBCe1 activity in rat PTs.…”
Section: Pparγ Agonists Enhance Pt Na Transport Via Wnk1/osr1mentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that PPARγ agonists enhance PT Na transport via ERK-mediated non-genomic effects 10,11 . We found that pioglitazone (PGZ), a PPARγ agonist, stimulated NHE and NBCe1 activity in rat PTs.…”
Section: Pparγ Agonists Enhance Pt Na Transport Via Wnk1/osr1mentioning
confidence: 99%
“…PTs were isolated as previously described [9][10][11][12] . PT was isolated from human and rat kidney cortex.…”
Section: Pt Isolationmentioning
confidence: 99%
See 3 more Smart Citations